O present perfect no discurso jornalístico na mídia digital - Frade, Celso (2008)
The present perfect (PrP) is a complex issue for researchers and non-native speakers of English that has been studied from many different perspectives. This research aims at showing a description of the PrP in the language of news media and brings to light new insights into the teaching of English as a foreign language. Linguistic research on the nature of news stories has seen a great increase since the 1970s. So, the theoretical underpinning for the research provides a briefing of the state-of-the-art literature on the area that includes views on tense and aspect, Travaglia (1985) and Comrie (1985), the usage of PrP according to Schwenter (1994), Michaelis (1998), Engel & Ritz (2005)) and Nishiyama & Koenig (2005, 2006) and the meaning of discourse by Bell (1991), Fowler (1991), Halliday (1978, 1985) and Fairclough (1995, 1999). It, therefore, provides a clear picture of what has been researched on the uses of the PrP and its various functions in the language of news media. More specifically, the research reported here, which used the documentary research methodology (Sanghera:2002), uses examples from the data collected, which include 60 sample articles from the websites of quality British and American broadsheets, such as The Guardian and The Independent (UK), The New York Times and The USA Today (USA), the website from the TV news broadcasters, BBC and CNN as well as from weekly magazines such as Newsweek and Time, which serve the purpose of illustrating both the occurrence and usage of the PrP in different contexts. The period sampled refers to the years 2003-2008 and the range of topics and subgenres include hard news (current events and one-off unscheduled events called spot news) and soft news (longer featured articles on different issues which are not time-bound to immediacy). The research question investigated in the study is: what kind of functions emerge from the PrP samples in the language of news media? With respect to the question, the results indicate the PrP is a means of intensifying the information according to specific pragmatic needs the producer has while writing the piece of news. Therefore, this study brings an original contribution to the existing body of research on the expression of time in TESOL and Applied Linguistics